Evolution and modern trends in the development of operational and investigative activities - Tuz , Oleksandr; Tyshchuk , Viktor (Actual problems of law (Aktual’ni problemi pravoznavstva), 2025)
The article examines the development of operational and investigative activities and their current state amid rapid changes in the criminal situation and new challenges law enforcement agencies face. The authors explore the stages of the evolution of approaches to conducting operational and investigative measures, starting from using simple methods of information gathering and ending with applying the latest technologies. This significantly enhances the efficiency of law enforcement work and dramatically expands the possibilities for investigating complex and multifaceted crimes. Special attention is given to how changes in the criminal situation in the country and globally have influenced the need to modernize operational and investigative activities methods. The rise of cybercrime, terrorism, drug trafficking, illegal migration, and other forms of organized crime requires the constant adaptation of operational tactics. Changes in these areas not only necessitate the implementation of new technologies but also demand an update in approaches to processing and utilizing information. Another critical aspect of the article is considering the legal framework for operational and investigative activities. Operational and investigative work must be conducted within the boundaries of the law, which not only defines the legal principles but also obliges operatives to strictly adhere to human rights, which becomes a challenge in combating new threats. The authors emphasize the need to improve legislation to correspond to new realities, particularly in addressing cybercrime, terrorism, and other emerging challenges. Thus, the article highlights that the continuous improvement of methods and tactics in operational and investigative activities is an integral part of effective crime fighting in the modern world.